Drivers' Responses to Countdown Timer at Signalized Intersection - Supiyono; Ludfi Djakfar; Achmad Wicaksono (Transactions on Transport Sciences)
Countdown Timers (CT) have gained significant popularity in recent years not only in many countries but also in Indonesia, particularly in the provinces of Central Java and East Java. CT displays the remaining seconds in numbers clearly before switching the traffic light on or off after a period of time. Three seconds before the light is to be off, drivers prepare to slow down the vehicles. On the contrary, some speed up to hasten the vehicles. The contrast behaviors represent different responses to traffic signals in an intersection. There are contradictions found in a number of previous studies as using a CT has potential advantages and disadvantages. One advantage is the driver is more prepared to continue riding. The disadvantage is the driver manipulates the countdown to speed up by yellow to red signals. To be objective, the data were obtained from the results of questionnaire based on a Likert Scale with eight variables out of 100 respondents of Sragen, 175 of Probolinggo, and 390 of Malang. The data were tabulated and analyses were carried out using Binary Logistic Regression. The results of the research are expected to be able to strengthen the previous findings. It can be concluded that CT is not necessary intall at the signalized intersection which can be the referrence for the further researches.